How investor attention affects stock returns? Some international evidence - Sergen Akarsu; Ömür Süer (Borsa Istanbul Review, 2022)
We examine the effects of limited investor attention on stock returns by using Google search volume index to measure investor attention. We also investigate whether national culture and market development have any role in this relationship. We find that the impact of investor attention on stock returns is not consistent throughout the world. The direction and significance of the impact vary from country to country. We also find that investor attention is more significant in individualistic countries, countries with high uncertainty avoidance, and developed countries. Furthermore, we find that the impact of abnormal returns on investor attention is more consistent across countries. One-week lagged absolute abnormal returns can positively predict investor attention in sixteen countries. Our results also show that investor attention returns to normal levels in three weeks in individualistic countries and countries with low uncertainty avoidance.